Orally Administered Crocin Protects Against Cerebral Ischemia/Reperfusion Injury Through the Metabolic Transformation of Crocetin by Gut Microbiota - Zhang, Yue; Geng, Jianliang; Hong, Yu; Jiao, Li; Li, Shuning; Sun, Runbin; Xie, Yuan; Yan, Caixia; Aa, Jiye; Wang, Guangji (Frontiers in Pharmacology, 2019)
Our pilot study suggested that orally administered crocin was hardly absorbed into circulatory system, but it was effective against cerebral ischemic/reperfusion (I/R) injury. The pharmacologically active component and targeting site of crocin remain elusive. In this study, the cerebral-protective effect of crocin was evaluated on a rat transient middle cerebral artery occlusion (MCAO) model. Our data showed that oral administration of crocin had better effectiveness in cerebral protection than an intravenous injection. Neither crocin nor its metabolite crocetin were determined in the brain of cerebral I/R rats, indicating a target site of periphery. Abundant crocetin was detected in plasma after oral administration instead of intravenous injection of crocin. Meanwhile, orally administered crocetin showed similar cerebral protection to that of crocin, but this exciting effect was not clearly observed by intravenous administration of crocetin, indicating the importance of crocetin in gut. Moreover, orally administered crocin showed less cerebral-protective effect in pseudo germ-free (pGF) MCAO rats. In vitro and in vivo experiments confirmed that crocin could be deglycosylated to crocetin in gut content of normal rats, rather than that of pGF rats, indicating that gut microbiota facilitated the transformation of crocin into crocetin, which played a key role in the activation of the pharmacological effect. Metabolomic study revealed that microbial-host co-metabolic molecules were significantly perturbed after oral administration of crocin, indicating a regulation on intestinal ecosystem. It was further suggested that gut microbiota may be the potential target of the cerebral-protective effect of crocin.